The gametogenic cycle of the non-native false limpet Siphonaria pectinata (Linnaeus, 1758) in the easternmost limit of its distribution range: implications for its future in the Eastern Mediterranean Basin - SLAMA, TASNIME; KEFI-JAAFAR, FERDAOUS; MAATOUG-BÉJAOUI, JIHÈNE; LAHBIB, YOUSSEF; HERMET, SOPHIE; RIVERA-INGRAHAM, GEORGINA; LIGNOT, JEHAN HERVÉ; MENIF, NAJOUA TRIGUI (Mediterranean Marine Science, 2020)
The gametogenic cycle of the false-limpet Siphonaria pectinata from the Bizerte channel (Northern Tunisia) was studied through histological characterization of the hermaphroditic gonad during a 1-year study period (May 2015 - May 2016). Spawning intensity in the field as well as the gonadic index were calculated monthly. Both female and male gametes were observed simultaneously within acini of adult individuals and continuously throughout the year. Oogenesis started in the mid-autumn (October), with gonads characterized mainly by proliferation of female cells. After that, oocytes progressively increased in number and volume until summer, when the evacuation stage frequency was the highest. From summer to autumn, some acini were empty from their oocyctes while some others had already begun the proliferation stage, suggesting the lack of a resting phase. Spermatogenesis was also a continuous process throughout the year, with spermatozoa being mainly observed in late spring (March). These findings suggested that environmental conditions are suitable for the establishment of S. pectinata, first mentioned in 1998 on the Tunisian coast and even suggest that it could continue spreading eastward in the Mediterranean Basin.